Reputation: 1293
This works:
assert(p(X) :- q(X)).
This does not work:
P = p,Q = q, assert(P(X) :- Q(X)).
How can I make the latter work?
Upvotes: 1
Views: 776
Reputation:
You need to make the terms first; you can use the "univ" operator, =..
for this:
?- P = p, Q = q, Head =.. [P, X], Body =.. [Q, X], assertz((Head :- Body)).
P = p,
Q = q,
Head = p(X),
Body = q(X).
?- listing(p/1).
:- dynamic p/1.
p(A) :-
q(A).
You need the second pair of parentheses in most implementations, apparently. You will need them anyway if you had for example a conjunction in the body.
?- assertz(a :- b).
true.
?- assertz(a :- b, c).
ERROR: assertz/2: Uninstantiated argument expected, found c (2-nd argument)
?- assertz((a :- b, c)).
true.
Upvotes: 4